Soil structure and glyphosate fate under no-till management in the Pampa region. I. Soil structural anisotropy and hydro-physical behavior - Behrends Kraemer, Filipe (2022)
Several studies have reported a frequent occurrence of platy structures in soils under no tillage (NT), mostly in silty ones. The objective of this study was to evaluate the morphological features and the pore architecture of a soil under NT and their effects on hydro-physical variables. The study was conducted on a Typic Argiudoll in a site located in the Rolling Pampa, NE of the Buenos Aires province, Argentina. The experimental area was a patch 50 m2, in which rainfall simulation and soil sampling were performed in four sub-plots. Soil structural features were determined by direct visual observation of monoliths and individual aggregates, and by micromorphological and micromorphometric analyses on thin sections. Occurrence of platy structure resulting from cultivation was evident in all sub-plots. A strong vertical anisotropy characterized the topsoil and different morphological types (Platy, Open Platy and Dense) were identified.Rainfall simulations were employed to determine infiltration rate, runoff and sediment yield, which show a high spatial variability. Total porosity, pore size and type and orientation of aggregates and pores appeared to be the main factors explaining the slow infiltration and the great variability of hydrological parameters. The results obtained indicate that a detailed study of structure and porosity of soils cultivated under NT can help to evaluate the effects of this practice on their physical health and behavior.